Predictors of Burnout Syndrome in Dentistry Students - Bonafé, Fernanda Salloume Sampaio [UNESP]; Maroco, João; Campos, Juliana Alvares Duarte Bonini [UNESP] (Leibniz Institute for Psychology (ZPID), 2014)
Aims: To estimate the contribution of social support and demographic factors in the development of burnout syndrome in dentistry students. Method: A total of 169 Brazilian students participated via internet. For identification of the syndrome, we used the Maslach Burnout Inventory (MBI-SS). Social support was assessed by the Satisfaction with Social Support Scale (ESSS). The validity and reliability of the instruments were estimated. To check the effect of variables on burnout syndrome, linear regression using structural equation modelling (SEM) was performed to estimate causal trajectories (β). Results: The participants’ mean average age was 21.6 (SD = 3.3) years, 64.5% were female and 59.2% were enrolled in private schools. An appropriate adjustment of the instruments’ factor models to sample was observed (MBI-SS: χ²/df = 2.173, CFI = .943; GFI = .888; RMSEA = .084; ESSS: χ²/df = 2.378, CFI = .904; GFI = .888; RMSEA = .091). The reliability of the scales was adequate (MBI-SS: α = .799-.903; ESSS: α = .653-.799). The model explained 33% of the variation of burnout with a significant contribution of social support (ESSS) (β = -.136, p = .042), gender (β = -.186, p = .005), housing (β = .124, p = .050), student performance in the course (β = -.293, p ≤ .001) and the thought of quitting the course (β = .333, p ≤ .001). Conclusion: Social support and demographic variables may play an important role in the burnout syndrome and therefore should be considered when implementing preventive actions and/or interventions (self-help or guided) in college students.
Keywords: Occupational health; Burnout; Social support; Psychological adjustment; Dentistry